Peta Genetika Tanaman, Prinsip dan Aplikasinya - Memen Surahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2002)
A complete genetic map, including genetic markers for all regions of all the chromosomes in a genome, serves .as framework,for determining the location of genes responsible for variat!on in plant growth and development. Strategies for mapping both discrete and contino us phenotypes are well - established as are efficIent experlmental approaches which minimize the time and cost of genetic mapping. GenetIc map represents a powerful tool In studying the basIs of variation in plant growth and development, and in testing hypothesis. about possible candidate genes. Moreover, genetic mapping serves as starting point for cldning genes, the function (s) of whIch are known only from mutant phenotypes. Key Words.. Genetic map, Linkage, Genome